(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This research after financial ratios in the detection of fraud to the financial statements published which enables specialists from the work of their studies and their conclusions to obtain the information they seek on the activities of the entity. Has provided researchers what these relics They then field study to test the validity and sincerity of the findings of the suggestions that have been upheld the need to study all financial ratios extracted in general, organized and used in decision-making processes necessary administrative.And that the financial management attention more financial analysis and extraction of financial ratios and compare them with industry standards taken from historical norms